Screening, isolation, identification and evaluation of bacteria with probiotic potential from traditional palmyra palm nectar - Kanimozhi, Raman; Sangavi, Ravichellam; Malligarjunan, Nambiraman; Gowrishankar, Shanmugaraj (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionTraditional fermented foods are rich reservoirs of probiotic microorganisms, yet several remain scientifically underexplored. The current research focused on the screening, isolation, identification, and assessment of potential probiotic isolates exhibiting β-galactosidase activity from naturally fermented Palmyra palm (Borassus flabellifer) nectar, a culturally significant, traditional beverage consumed in India.MethodsA total of 80 bacterial isolates were obtained under aseptic conditions and screened through cultural, microscopic, and biochemical analyses. Fifty-six Gram-positive, catalase-negative isolates were shortlisted for probiotic evaluation. Selected isolates were assessed for simulated gastrointestinal conditions, cell surface properties (auto-aggregation, hydrophobicity, co-aggregation and Biofilm production), β-galactosidase and exopolysaccharide production, antioxidant activity, antibiotic susceptibility, and safety through hemolysis and DNase activity.ResultsSeventeen isolates exhibited desirable adhesion-related traits, of which seven strains demonstrated superior probiotic potential. These strains tolerated acidic and bile conditions, produced high levels of exopolysaccharides (573-785 mg/L) and β-galactosidase (110.25-221.09 U/mL), and showed significant cell surface hydrophobicity (35.87-69.93%), auto-aggregation (59.29-82.76%), and co-aggregation with pathogens Salmonella Typhi (MTCC 733) 46.58 - 70.87% and S. flexneri (ATCC 12022) 53.45 - 78.85%. They also exhibited substantial hydroxyl radical scavenging activity (57.68-70.66%) and were safe and antibiotic-susceptible.DiscussionThe findings highlight the probiotic potential and functional attributes of Palmyra nectar - derived bacteria. Their ability to survive gut-like conditions, hydrolyze lactose, adhere to intestinal mucosa, and provide antioxidant benefits supports their application in functional foods and nutraceuticals aimed at improving gut health and lactose digestion.